University-Level Kurdish EFL Teachers’ Perceptions of Assessment: Purpose, Design and Validity, Reliability, and Practicality - Murad, Ivan; Sanan Shero Malo (Universitas Cokroaminoto Palopo, 2026)
Within educational systems, assessment is regarded as a central element of the educational process, shaping teaching and learning and guiding instructional practices and learning outcomes. Nonetheless, the impact it makes on the educational process is hugely contingent upon teachers’ perceptions, beliefs, and attitudes regarding assessment practices. This is because the way teachers value assessment determines the way it is used in their classrooms. The current study tries to study the perceptions of university-level Kurdish EFL teachers’ perceptions of assessment in terms of the purposes it serves, the way it is designed, its validity, reliability, and practicality. To achieve this aim, a mixed-method approach is employed, utilizing a survey and semi-structured interviews for data collection. The samples of the study included 110 teachers responding to the survey especially designed to gather quantitative data for the study, and 16 teachers volunteered to be interviewed to provide more in-depth data for the study. A random sampling strategy was followed so that every teacher has a chance to participate in the study. The quantitative data was analyzed using SPSS version 25, whereas a thematic approach was used to analyze the qualitative data following Braun and Clarke’s (2006) six-step framework of analysis. Results revealed that teachers perceive the purpose of assessment as effective and serving multiple purposes. Regarding the design and validity of assessment, their perception was generally positive; however, they see that the design of assessments needs to effectively address a diverse level of students. Positive perceptions were found regarding the reliability of assessment. However, they perceive the grading process as weak and not consistent across teachers. Finally, teachers have positive perceptions of the practicality of assessment.